"COMPARATIVE STUDY OF TIME-MEANING PAREMIOLOGICAL UNITS IN ENGLISH AND UZBEK" - Zayniddidin Narmuratov Rajapovich; Safarmurodova Maftuna To’raqulovna (Western European Studies, 2025)
Paremiological units, commonly referred to as proverbs or phrases, are an integral part of language and culture in every society. These short and meaningful statements encapsulate traditional wisdom and reveal the mindset and values of a particular community. The study of paremiology focuses on understanding the semantic, syntactic, and pragmatic aspects of these linguistic expressions. In this intersectional study, we analyze the temporal meanings of paremiological units in both English and Uzbek languages, aiming to identify cultural similarities and differences.
Keywords: paremiology; paremiological unit; proverb; phrase